Rational Choice Virtues - Verbeek, Bruno (Ethical theory and moral practice, 2010)
In this essay, I review some results that suggest that rational choice theory has interesting things to say about the virtues. In particular, I argue that rational choice theory can show, first, the role of certain virtues in a game-theoretic analysis of norms. Secondly, that it is useful in the characterization of these virtues. Finally, I discuss how rational choice theory can be brought to bear upon the justification of these virtues by showing how they contribute to a flourishing life. I do this by discussing one particular example of a norm - the requirement that agents to honor their promises of mutual assistance - and one particular virtue, trustworthiness.